Phenotypic and genotypic characterization of double carbapenemase producing Enterobacterales in a University Hospital (Actualizaciones en Sida e Infectología, 2023)
The emergence of double-carbapenemase (KPC and NDM) producing Klebsiella pneumoniae isolates is one of the consequences derived from the SARS CoV-2 pandemic, which has caused significant impact on the antimicrobial resistance rates in hospital acquired infections. These isolates represent a real challenge for Health Services due to their difficult detection and characterization and subsequent treatment. In the present work we describe the double carbapenemase producing isolates recovered during the year 2022 from clinical samples belonging to hospitalized patients at a University Hospital in Buenos Aires city, we report their phenotypic and genotypic characterization and the excellent activity of the ceftazidime-avibactam-aztreonam combination in the treatment of infections in which the therapeutical options are restricted to non β- lactamic antimicrobials which hold resistance rates higher than 70%.
Keywords: Klebsiella pneumoniae, double carbapenemase, KPC, NDM